OPTIMIZATION OF THE RHEOLOGICAL PARAMETERS OF PILOT LIQUID DOSAGE FORMS IN THE DEVELOPMENT OF SPRAY PREPARATION AND TECHNOLOGY FOR ORAL CAVITY DISEASES TREATMENT - P. G. Mizina; S. M. Levachev; P. M. Masese; A. V. Panov; A. E. Harlov; N. V. Sugak; D. O. Shatalov (Разработка и регистрация лекарственных средств)
Theoretically substantiated and experimentally determined viscosity and adhesive properties of the experimental compositions of the liquid formulation with plant extracts of Eucalyptus (evkalimin) and Echinacea purpurea (estifan). It proved that are designed mucoadhesive pharmaceutical compositions that might provide a sustained action on the surface of the oral mucosa.